A Case of Pulmonary Infarction Resembling Pneumonia during Immunosuppressive Treatment for Rheumatoid Arthritis - Toshiki Kido; Koichiro Shinoda; Kazuyuki Tobe (Case Reports in Rheumatology)
A 67-year-old woman with rheumatoid arthritis (RA) presented with fever and dyspnea. Chest radiography and computed tomography (CT) revealed pulmonary infiltrates with ground-glass opacities. We considered bacterial or pneumocystis pneumonia because she was immunocompromised due to RA treatment. However, she had tachycardia and elevated D-dimer levels. We performed contrast-enhanced CT and subsequently diagnosed her with pulmonary embolism (PE). Though PE is not usually accompanied by parenchymal pulmonary shadows, pulmonary infarction may cause pulmonary infiltrates that can be mistaken for pneumonia. As RA is a thrombophilic disease, clinicians should be aware of PE and pneumonia as differential diagnoses in such patients.